An Analysis of Evaluation Methods Implemented in Studies Published in the Journal of International Agricultural and Extension Education from 1994 to 2018: A 25 Year Review - Theresa Pesl Murphrey; Taniya J. Koswatta; Kim E. Doody; Leslie D. Edgar (Journal of International Agricultural and Extension Education, 2018)
Evaluation has been identified as a critical pathway to meet the grand challenges facing agricultureto feed the world.Understanding evaluation models and practicesused in articles published in the Journal of International Agricultural and Extension Education(JIAEE) allowedus to identify areas of focus, need, and improvement. This content analysisassessed JIAEEarticlespublished from 1994 to 2018 for evaluation methods implemented according to characteristics outlined by Stufflebeam and Coryn (2014). This study initially identified 384 possible articles for consideration. Upon further assessment,81 articles were identified asmaintainingcharacteristics appropriate for review.Of these articles, the majority (70%) did not specifically identify an evaluation approach, even though21% of all feature articles published over the past 25 years can be considered an evaluation. Few published evaluationarticles specifically identified an evaluation approach;rather,the majority merely described the methods without using evaluation terminology, and the majority of the examined articles did not substantially cite evaluation literature(53%).Additionally, the majority of published evaluation articles were quantitative (56%).Researchers publishing in JIAEEshould be assured that qualitative and mixed method evaluation studies arealso acceptable. Evaluationstudies focused on Stufflebeam and Coryn’s evaluation criteria offeasibility, safety, equity, and probity should be encouraged. Additionally, workshops or training opportunities to advance understanding in evaluation processes and procedures may be valuable
Keywords: Evaluation; Evaluation Methods; Content Analysis; JIAEE